Remote Sensing-Based Urban Environmental Quality Indicators: A Review - Nurwita Mustika Sari; Dwi Nowo Martono; Raldi Hendrotoro Seputro Koestoer; Dony Kushardono (Journal of Multidisciplinary Applied Natural Science, 2025)
Most of the global population lives in urban areas, which also serve as hubs of economy, industry, and government activities. Various factors that affect the quality of cities have been studied in different locations. This article reviews various papers that examine environmental quality indicators in urban areas that can be extracted from remote sensing data. The first aspect is vegetation cover, which is known from the vegetation index normalized difference vegetation index (NVDI), and the second aspect is surface temperature, which is known from land surface temperature (LST). In this work, urban environmental conditions in various countries are compared with urban conditions in Indonesia based on these indicators. It is found that NDVI and LST are indicators from remote sensing that are widely used to analyze urban environmental conditions. The vegetation index has a negative correlation with surface temperature. High surface temperature creates discomfort in urban quality of life and brings mental stress to residents living in those areas. Based on bibliometric analysis and network map, it is known that there are 30 most relevant words or terms to the keywords “urban remote sensing” and “remote sensing environment indicator” with the highest frequency of occurrence and relevance. This study can serve as input for the government as policymakers and urban planners to formulate spatial planning policies oriented towards sustainability and to research current topics related and relevant to remote sensing-based urban environmental quality indicators.